SUMBANGAN TAMADUN ISLAM DALAM KEHIDUPAN MASYARAKAT DI ALAM MELAYU HINGGA ABAD KE-17 M - Mohammad, Ali (Journal of Al-Tamaddun, 2008)
The advent of Islam in the Malay World affected the life of the societies a great deal. The present article aims at discussing about several changes and renewels which were introduced by Islam in various aspects of life such as aqidah and thinking, society and law, politics and knowledge, language and writing which were initiated from the beginning of Islam till the 17th century. The changes introduced by Islam turned the Malays into a developed nation on the basis of Islamic Civilization.